PELATIHAN MENULIS CERPEN HOROR UNTUK PELAJAR SMA BRUDERAN PURWOREJO JAWA TENGAH DENGAN TEKNIK PENGINDRAAN - Yudono, Kristophorus Divinanto Adi; Margareta, Yustina Yuyu; Bintoro, Putri (Jurnal Abdimas Musi Charitas, 2024)
This community service activity aims to provide guidance on writing short horror stories using sensory techniques for students of Bruderan High School, Purworejo, Central Java. The activity was conducted based on a needs analysis of the partner through questionnaires and interviews. The implementation was carried out at the Bruderan High School Auditorium in Purworejo, Central Java, with participation from students of various levels, accompanied by their Indonesian language teachers. The methods used in this activity included several stages, such as school needs analysis, focused group discussions on horror writing using sensory techniques, practical horror story writing, presentation of the horror stories, and discussions on the outcomes. This activity resulted in each participant producing their own short horror story. These stories were included in various writing activities, such as anthology publications and short story competitions. Additionally, students at Bruderan High School are able to apply sensory techniques in their short story writing.